Adoption of Sustainable Dairy Management Practices and its Effect on Farm Income: A Case of Dairy Farmers in Rubaya Sub-County, Mbarara District - Muhumuza, Ronnie; Ssemakula, Edward; Kalibwani, Rebecca (East African Nature and Science Organization, 2024)
Sustainable dairy management (SDM) practices aim to minimize environmental impact, promote animal welfare, ensure economic viability, and support social responsibility throughout the dairy production chain. The SDM practices that could improve sustainability of dairy farming systems in Uganda include milk management, animal health, feeding and breeding practices. Despite the numerous advantages that scientific literature reports for these dairy management practices, they are not always adopted by farmers because of various factors. The objectives of this study were to examine farmers’ adoption decisions towards Sustainable Diary Management (SDM) practices, as well as the economic impact of this adoption among dairy farmers in Rubaya Subcounty. The cross-sectional research design was applied to collect both quantitative and qualitative data using a semi-structured questionnaire. Data were collected using a household survey of 160 randomly selected respondents, from different villages within the study area. R Software Version 4.4.0 was used for data analysis. The results reveal that most of the SDM practices were adopted by over 50% of the dairy farmers. Only Artificial insemination, drying off animals, conservation fodder and concentrate feeding practices were adopted by less than 50% of the dairy farmers. The Multivariate logistic regression model results show that the adoption of SDM practices is significantly associated with varied demographic (Gender, age, household size); socio-economic (land size and household income); and institutional factors (access to agricultural credit, access to extension services, and membership to a farmer association). The study found out that adoption of SDM practices increased their farm income by UGX. 2,930,429/=, highly significant at 5% (p=0.02). The study recognizes two main pathways to increase the adoption of SDM practices: i) utilizing farmers’ knowledge and information sharing platforms; and addressing broader market and institutional failures